An Analysis of the Students’ Difficulties in Understanding Poetry - Mastura Mastura (English LAnguage Study and TEaching, 2022)
For Indonesian EFL (English as a Foreign language) learners, learning poetry in English is difficult. The purpose of this study is to know the difficulties in understanding poetry faced by students of the English Department of Universitas Serambi Mekkah. The total sample was 23 students from Semester 5 and 7 who had taken Poetry and Drama subject. This research is a descriptive method using a questionnaire and interview for the data collection. The finding shows that students have difficulties in understanding figurative language, proverbs, and the meanings of poetry. The interview data revealed the reluctance of the students in learning the subject. To conclude, the English Department students of Universitas Serambi Mekkah have poor English knowledge and low motivation towards learning the subject thus facing difficulties in understanding English poetry. It is suggested that the lecturer should use several strategies to make students motivated and ignite creativity among students when learning English poetry.